PERSONALITY STRUCTURE: ORTHOGONALITY VERSUS OBLIQUITY - Ruiz, Victor Manuel; Jiménez, José Antonio (Anales de Psicología / Annals of Psychology, 2004)
In this report, the problem of the lack of simplestructure and the controversial issue of orthogonality vs.obliquity with regard to the Five-Factor Model of personality are analysed through the Spanish version of the Big Five Questionnaire (BFQ; Caprara, Barbaranelli, Borgogni y Perugini, 1993). The sample was made up of 289 subjects (113 men and 176 women) from the general population, in a range from 18 to 65 years old. Exploratory and confirmatory factor analysis results point to a mixed model, that assumes both orthogonality between some factors and obliquity between some others, which shows the best balance between goodness-of-fit and parsimony. Finally, results and their implications for future research are discussed.